2010
DOI: 10.3109/09537101003718065
|View full text |Cite
|
Sign up to set email alerts
|

The role of prostanoid receptors in mediating the effects of PGE2on human platelet function

Abstract: The effects of prostaglandin E(2) (PGE(2)) on platelet function are believed to be the result of opposing mechanisms that lead to both enhancement and inhibition of platelet function. Enhancement of platelet function is known to be via EP3 receptors linked to G(i) and inhibition of adenylyl cyclase. However, the receptors involved in inhibition of platelet function have not been fully defined. Here we have used measurements of platelet aggregation, calcium signaling and P-selectin expression to assess platelet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 33 publications
2
35
1
Order By: Relevance
“…A negative effect of butaprost on PAF-induced platelet aggregation has also been reported (Matthews and Jones, 1993;Iyú et al, 2010). Butaprost did not modify intraplatelet Ca 2ϩ , with or without ADP, whereas it promoted VASP-P, indicating a cAMP-mediated effect, which is consistent with previous data on different cells (Regan et al, 1994).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…A negative effect of butaprost on PAF-induced platelet aggregation has also been reported (Matthews and Jones, 1993;Iyú et al, 2010). Butaprost did not modify intraplatelet Ca 2ϩ , with or without ADP, whereas it promoted VASP-P, indicating a cAMP-mediated effect, which is consistent with previous data on different cells (Regan et al, 1994).…”
Section: Discussionsupporting
confidence: 82%
“…The data of 17-phenyl-trinor PGE 2 (EP3 Ͼ EP1 agonist based on K i values; Kiriyama et al, 1997), mimicking 11d-16dm PGE 2 on VASP-P, microaggregates, and P-selectin expression, further support this hypothesis. Our results are consistent with and extend previous data (Heptinstall et al, 2008;Iyú et al, 2010), but we used diverse PGE 2 analogs, calculated the EC 50 values, ranked potency profiles on specific effects (enhancement of the secondary aggregation, stabilization of aggregates), and explored different platelet agonists at various concentrations. Furthermore, this is the first description of 11d-16dm PGE 2 -responsive receptors on platelets.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The amounts of the phosphorylated form of VASP present in the lysates were measured by flow cytometry using a cytometric bead assay, which has been described previously. 5,31 The assay was developed using Becton Dickinson Cytometric Bead Array products as described below.…”
Section: Measurement Of Phosphorylation Of Vaspmentioning
confidence: 99%
“…1). Recent studies have shown that platelet function is regulated via several prostanoid receptors expressed in platelets, including EP 2 (Kuriyama et al, 2010;Smith et al, 2010), EP 3 (Fabre et al, 2001;Ma et al, 2001), EP 4 (Iyú et al, 2010;Kuriyama et al, 2010;Philipose et al, 2010;Smith et al, 2010), IP (Murata et al, 1997), and TP (Thomas et al, 1998). Among these receptors, EP 2 and EP 4 , in addition to IP, mediate inhibitory signaling in platelets.…”
Section: Discussionmentioning
confidence: 99%